Вплив поперечних струмів на вхідний імпеданс збуджувача вібраторного типу у хвилеводі - Захарія, Й.А. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
Use the example of thin strip waveguide exciter input impedance analysis it is the existence of transverse electrical currents on the exciter surface established. More influential are these currents on the broad strip-exciter surface located in the waveguide-crossection plane. Tranverse currents reduce the value of input resistance, and enlarge the value of input reactance. For sufficient high analysis accuracy it is necessary transverse currents on the waveguide-exciter surface to consider.